Analisis Performa Protokol 6LoWPAN pada Jaringan Sensor Nirkabel Menggunakan Cooja Simulator - Wawan Darmawan; Sabriansyah Rizqika Akbar; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
6LoWPAN (IPv6 over Low power Wireless Personal Area Networks), is an IPV6-based protocol that allows devices with small power consumption such as fixed sensors to connect and participate in IoT (Internet of Things) with greater scalability. This research simulate 6LoWPAN protocol on wireless sensor network (WSN) using Cooja simulator. Wireshark then used to analyse QoS (Quality of service) parameters, that is throughput, delay and jitter to know the performance of 6LoWPAN. Simulator is used because building a genuine propagation network takes a lot of time and costs. From the results of simulation that use cluster-based topology involving 10 clusters and routing protocol for low power and lossy network (RPL), the acquisition of throughput, delay and jitter based on Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON) showing a good results. the highest throughput is obtained by Cluster 1 with 206 bps, the lowest delay was obtained by cluster 7 with 56 ms and the lowest jitter also obtained by cluster 7 with 0.003 ms. It can be concluded that the 6LoWPAN protocol performance on wireless sensor network is very good, consider the high throughput value with low delay and jitter value